Implementing findings of research. - Haines, A. (BMJ Group, 1994)
There are unacceptable delays in the implementation of many findings of research. This results in suboptimal care for patients. A number of approaches may be effective in speeding up implementation, including evidence based guidelines, the influence of opinion leaders, and computer based decision support systems. An integrated approach to speeding up this process by means of a number of mechanisms is likely to be most effective. The results of systematic reviews of the research literature should be incorporated into programmes of continuing medical education and clinical audit. Professional associations have an important role to play in ensuring that research based information is included in educational activities and clinical guidelines. Purchasers of health care could promote the uptake of research findings during contract negotiations. Improved methods of informing health care users and the public about evidence of effectiveness could also have an impact. Policy makers should take more account of the results of research when formulating recommendations. Methods of improving the implementation of research findings require further investigation and greater resources devoted to them.